Cold‐Aging and Solvent Vapor Mediated Aggregation Control toward 18% Efficiency Binary Organic Solar Cells. Issue 39 (28th August 2021) - Guo, Chuanhang; Li, Donghui; Wang, Liang; Du, Baocai; Liu, Zhi‐Xi; Shen, Ziqiu; Wang, Pang; Zhang, Xue; Cai, Jinlong; Cheng, Shili; Yu, Cong; Wang, Hui; et al.
Abstract: The molecular ordering and pre‐aggregation of photovoltaic materials in solution can significantly affect the nanoscale morphology in solid photoactive layers, and play a vital role in determining the power conversion efficiency (PCE) of organic solar cells (OSCs). Herein, a cold‐aging strategy is reported to mediate the pre‐aggregation of PM6 polymer in solution through a disorder‐order transition, which leads to dense and fine PM6 aggregates with enhanced π−π stacking in its blend thin films with either fused‐ring and non‐fused‐ring non‐fullerene acceptors (NFAs) including Y6‐BO, N3, IT‐4F, and PTIC. The fine aggregates of PM6 and slightly enlarged NFA domains improve the continuous networks with enhanced and balanced charge mobility. The resulting OSCs all demonstrate enhanced PCEs compared to their counterparts without any cold‐aging treatments, with PM6:Y6‐BO OSC being most effective from 16.6% to 17.7%, demonstrating the universality of this approach. This can be further optimized upon casting of the cold‐aging solution with the presence of solvent vapor, resulting in a champion PCE of 18.0% for PM6:Y6‐BO OSC, which is the highest PCE of this OSC reported in the literature. This work provides a rational guide for optimizing non‐fullerene OSCs via aggregation control before and during the solution casting process. Abstract : A cold‐aging induced aggregation approach is demonstrated to enhance device efficiency of organic solar cells via tuning of the pre‐aggregates of polymer donor PM6 in solution and therefore in its solid photovoltaic blend films with a range of fused‐ring and non‐fused‐ring non‐fullerene electron acceptors.